Navigating the feminine in massively multiplayer online games: gender in World of Warcraft - Brehm, Audrey (Frontiers in Psychology, 2013)
The objective of the study is to present and discuss attitudes, perceptions and opinions about sexism and gendered play in the massively multiplayer online roleplaying game (MMO), World of Warcraft. Through the use of an online survey which includes both multiple choice questions and open-ended questions, the research discusses the major themes and findings expressed by the World of Warcraft forum users (N = 294). The descriptive statistical findings presented are derived from the multiple choice questions. Within the sample, the results reveal that sexism is a contentious topic in the World of Warcraft community. 63.6% (n = 75) of female respondents reported experiencing sexism within the game. 27.5% (n = 44) of male respondents and 45.3% (n = 53) of female respondents believe that sexism is a problem in the game. Overall, 64.4% (n = 183) of the respondents reported sexism as a non-issue in the game. Themes surrounding the topic of sexism experienced within the game are presented based on frequency of homogenous responses. Based on the multiple choice questions and the open-ended questions, the research argues that sexism and gendered play in gaming should be studied more closely, as the results reveal that many MMO players are affected negatively by it.